Investigating optical properties of Cr:GaN system for various Cr concentrations (A DFT + U study). (27th May 2020) - Khan, M Junaid Iqbal; Liu, Juan; Kanwal, Zarfishan; Khan, Muhammad Ismail; Usmani, M Nauman; Khalid, Ata Ur Rahman
Abstract: We study electronic and optical properties of zincblende GaN doped with various Cr concentrations (3.12%, 6.25%, 9.37%). We conduct the calculations by employing DFT + U in Wien2K code while supercell size (1 × 2 × 2) is kept fixed for all cases. Electronic properties are changed with effect of dopant where 3 d levels of dopant and 2 p level of N pro d uce p - d hybridization and this hybridization is highly affected by increasing impurity contents. Absorption spectra are blue shifted upon increase in dopant contents and absorption peaks are more pronounced in UV region. Refractive index and dielectric constant shows decrease as Cr concentration increases. Results reported in study indicate that Cr:GaN material may be considered a potential candidate for fabrication of optoelectronic, photonic and spintronic devices.